Assessment of Industrial Impact on Groundwater Quality in N'Djamena, Chad - Idriss Mahamat Yaya; Mahamat Nour Abdallah; Khadidja Rozzi Kelleymi; Abderamane Hamit (Pakistan Journal of Analytical & Environmental Chemistry)
This research study aims to quantify the physicochemical parameters of groundwater in the Farcha district of N'Djamena with a specific focus on evaluating contamination caused by chemical discharge and industrial residues. The methodology involved data collection, lithological borehole sections, and physicochemical analysisof electric conductivity (EC), pH, total dissolved solids (TDS), turbidity, iron concentration, alkalinity, hardness, phosphorus concentration, oil presence, concentrations of chlorine, silica, and hydrogen sulfide. Sample locations were deliberately selected proximately closest to potential sources of contamination. Twenty groundwater samples (n = 20) were collected after flushing stagnant water from pipes. The resulting data indicated that the groundwater samples of studied areas were dominantlyhaving neutral to slightly basic pH with modest mineralization (95.2 – 334 μS/cm). The physicochemical quality parameters of the studied water samples were within the WHO permissible limits for drinking water. However, a noticeable increase in the amounts of iron and hydrogen sulfide was observed in sample E16 whilst sample E10 showed the elevated contents of silica and TDS. These contaminations are contributed by anthropogenic contamination from industrial wastewater infiltration and subsoil lithology.These concentrations are due to local geology or human activities, indicating vulnerability to pollution.